Barriers to Delivery Care by Skilled Attendants In North Sulawesi - Langia, F. L. Fredrik G.; Najoana, Johannis A. (Jurnal Kedokteran Indonesia, 2009)
Background: To investigate the barriers for women in North Sulawesi to accessing a skilled attendant at birth.Methods: A secondary data analysis of the 2002/2003 Indonesia Demographic and Health Survey which involved the most recent live birth in the past five years of 428 ever-married women aged 15-49 in North Sulawesi was performed. Independent variables were captured by the Andersen behavioral model. Multivariate analysis was conducted with logistic regressions.Results: By adjusting other factors, motherâs educational attainment was the only significant determinant for the use of a skilled attendant. The adjusted OR of the change in birth attendant in women with secondary or higher level of education was 2.58 (95%CI 1.35-4.93).Conclusion: Low educational attainment was a significant barrier for women in North Sulawesi to accessing professional delivery care. To improve access, health care authorities and providers would need to educate women about their reproductive health and familiarizing them with maternal health services. Jurnal Kedokteran Indonesia: 1 (1): 94-101Keywords: maternal health, delivery care, skilled attendant, health care utilization, Andersen behavioral model, North Sulawesi